Continuous‐Flow Synthesis of ZIF‐8 Biocomposites with Tunable Particle Size. (17th March 2020) - Carraro, Francesco; Williams, Jason D.; Linares‐Moreau, Mercedes; Parise, Chiara; Liang, Weibin; Amenitsch, Heinz; Doonan, Christian; Kappe, C. Oliver; Falcaro, Paolo
Abstract: Zeolitic imidazolate framework (ZIF) biocomposites show the capacity to protect and deliver biotherapeutics. To date, the progress in this research area is based on laboratory batch methods. Now, the first continuous flow synthetic method is presented for the encapsulation of a model protein (bovine serum albumin, BSA) and a clinical therapeutic (α1‐antitrypsin, AAT) in ZIF‐8. The in situ kinetics of nucleation, growth, and crystallization of BSA@ZIF‐8 were studied by small‐angle X‐ray scattering. By controlling the injection time of ethanol, the particle growth could be quenched by ethanol‐induced crystallization from amorphous particles to ZIF‐8 crystals. The particle size of the biocomposite was tuned in the 40–100 nm range by varying residence time prior to introduction of ethanol. As a proof‐of‐concept, this procedure was used for the encapsulation of AAT in ZIF‐8. Upon release of the biotherapeutic from the composite, the trypsin inhibitor function of AAT was preserved. Abstract : Genau richtig : Die Partikelgröße von ZIF‐8‐Biokompositen kann durch kontrollierte Injektion von Ethanol in die ZIF‐Vorläuferlösung präzise abgestimmt werden. Basierend auf dem abrupten Übergang von amorpher zu kristalliner Phase wurde eine Ethanol‐Quenchingmethode genutzt, um die Partikelabmessungen auf den Bereich 40–100 nm einzuschränken. Diese Durchflusssynthese ermöglicht die Anwendung von Biotherapeutika in ZIF‐8 für die Biomedizin.